Assessment Of Improvement Factors Violent Crimes In The United States - Anas Puja Kesuma; Adhi Cahya Fahadayna (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2023)
Abstract This article examines the phenomenon violent crime which is increasingly becoming a prominent issue in the United States, where researchers are trying to see the relationship between factors such as the freedom to own firearms in the United States and social and economic disparities as factors that encourage individuals to commit violent crime, by seeking justification for individual behavior as rational action when viewed from that perspectiveRational Choice Theory. It was found that despite the high level of firearms ownership in the United States it greatly influences activityviolent crime andviolent crime which leads to death, researchers still cannot prove that external factors such as social and economic inequality have a major influence on the motivation of the United States population to commit suicide.violent crime. Researchers then provide recommendations regarding efforts to mitigate the negative impacts of the factors that have been explained, which are expected to contribute to good research that has been carried out, as well as future research. Keywords: Firearm Ownership, Social and Economic Disparities, Violent crime